Body, Mind, and Plate: Exploring the Links between Sleep Quality, Perceived Stress, and Eating Behaviour among Medical Students in a Malaysian University - Ting, Chuong Hock; Muhammad Nur Ramadhan, Mazidi; Wan Fatin, Wan Bahrain; Kuan, Shi Min; Nurul Azah Afifah, Ariffin (2023)
Sleep quality is a well-recognized predictor of good physical and mental health. However, sleep deprivation and poor sleep quality are common issues among medical students, as they are expected to handle a demanding and rigorous curriculum, long hours of study, and clinical rotations, leading to stress and sleep problems. Previous research reported stress associated with unhealthy eating patterns. Hence, this study aims to evaluate the sleep quality of medical students and determine its association with perceived stress levels and eating behaviours. This cross-sectional study was conducted in a Malaysian public university from January to April 2022 using a simple random sampling method. The respondents completed a set of self-administered questionnaires. This includes their demographic data, Pittsburgh Sleep Quality Index (PSQI), Perceived Stress Scale (PSS), and Adult Eating Behaviour Questionnaire (AEBQ). Among the 339 respondents, 72% of the respondents were female students. We found a high prevalence of poor sleepers (60.5%). Only 23.5% slept more than 7 hours/day. 7.1% reported using sleeping medication in the past month. 67.6% and 20.9% reported moderate and high stress levels respectively. Poor sleepers had significantly higher stress levels (t=6.192, p<.001) and were significantly associated with food avoidance eating patterns (t=2.281, p=.023). Pearson correlation analysis showed a positive correlation between sleep quality and perceived stress level, emotional over-eating, emotional under-eating, hunger, and satiety response while negatively correlated with enjoyment of food. Multiple linear regression revealed the perceived stress level is the significant predictor of sleep quality. The university urgently needs to address sleep quality issues among medical students. The medical curriculum should also emphasis building their mental health resilience by providing them with skills and resources to adopt helpful stress management and healthy eating habits while maintaining good sleep hygiene to enhance their learning experience and academic performance.